Vertebrate hox temporal collinearity: does it exist and what is it's function?. Issue 5 (4th March 2019) - Durston, A. J.
ABSTRACT: Hox temporal collinearity (TC) is a mysterious feature of embryogenesis. This article is opportune because of a recent challenge to TC's existence This challenge is examined and the evidence that TC does exist is presented. Its function is discussed. Temporal collinearity is thought to be important because it lays the basis for Hox spatial collinearity and the vertebrate A-P axial pattern. The time-space translation mechanism whereby this occurs is examined.